The effect of improving physical fitness through traditional games in elementary schools - Surur, Muhammad; Gani, Ruslan Abdul; Rahayu, Ega Trisna; Gustiawati, Resty (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: Is through traditional games can improve physical fitness learning outcomes on PJOK Learning. Purpose: To know the improvement of physical fitness learning through traditional games. Methods: The research uses experimental methods with a pretest-posttest control group design. The research population was a fifth-grade student in Muaragembong district of Bekasi. The sample was selected using purposive sampling, which means students who have a low level of physical fitness based on the results of the Indonesian physical fitness test. (TKJI). The sample consisted of two groups, the experimental group and the control group, with a total of 15 students each. Results: The results of data analysis showed that there were significant differences between the experimental group and the control group on the posttest, with values t = -4,76 and p = 0,000 (p < 0.05). This means that the average level of physical fitness of the experimental group is higher than that of the control group after being treated as a traditional game. Conclusion: From the results of this study it can be concluded that learning PJOK using traditional game methods can improve the learning results of physical fitness.